Looking for the Optimal PD-1/PD-L1 Inhibitor in Cancer Treatment: A Comparison in Basic Structure, Function, and Clinical Practice - Chen, Yu; Pei, Yanqing; Luo, Jingyu; Huang, Zhaoqin; Yu, Jinming; Meng, Xiangjiao (Frontiers in Immunology, 2020)
Programmed cell death protein-1/ligand 1 (PD-1/L1) targeted immune checkpoint inhibitors have become the focus of tumor treatment due to their promising efficacy. Currently, several PD-1/PD-L1 inhibitors have been approved for clinical practice with several more in clinical trials. Notably, based on available trial data, the selection of different PD-1/PD-L1 inhibitors in the therapeutic application and the corresponding efficacy varies. Widespread attention then is increasingly raised to the clinical comparability of different PD-1/PD-L1 inhibitors. The comparison of the inhibitors could not only help clinicians make in-depth understanding of them, but also further facilitate the selection of the optimal inhibitor for patients in treatment as well as for future clinical research and the development of new related drugs. As we all know, molecular structure could determine molecular function, which further affects their application. Therefore, in this review, we aim to comprehensively compare the structural basis, molecular biological functions, and clinical practice of different PD-1/PD-L1 inhibitors.